2016
DOI: 10.1038/npjpcrm.2016.2
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in initial COPD treatment choice over time and factors influencing prescribing decisions in UK primary care: a real-world study

Abstract: Prescribing patterns in chronic obstructive pulmonary disease (COPD) are often inconsistent with published guidelines. This retrospective, observational study utilised data from the Optimum Patient Care Research Database to examine the changes in COPD prescribing patterns over time and to identify predictors of physician treatment choice for patients newly diagnosed with COPD. Initial therapy was defined as the treatment(s) prescribed at or within 1 year before COPD diagnosis. Changes over time were assessed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 25 publications
6
31
1
Order By: Relevance
“…Several other studies have reported undertreatment with bronchodilators in comparison with ICS [9,13], or a majority of patients receiving LABA/ICS without LAMA [16]. Rather few studies have investigated temporal change in treatment patterns, but our results of decreased proportions of patients with sole ICS treatment or no maintenance treatment at all over time are consistent with a study of COPD patients in UK primary care [12]. …”
Section: Discussionsupporting
confidence: 87%
“…Several other studies have reported undertreatment with bronchodilators in comparison with ICS [9,13], or a majority of patients receiving LABA/ICS without LAMA [16]. Rather few studies have investigated temporal change in treatment patterns, but our results of decreased proportions of patients with sole ICS treatment or no maintenance treatment at all over time are consistent with a study of COPD patients in UK primary care [12]. …”
Section: Discussionsupporting
confidence: 87%
“…The overall finding of this study—that the prescribing of long‐acting bronchodilators and ICSs in patients with COPD does not appear to align with GOLD guidelines—is consistent with recent studies based on subgroups of patients in a variety of settings. Our observation that the most commonly dispensed first regimen involving a long‐acting bronchodilator was a LABA in combination with an ICS is consistent with findings from Spain, the Netherlands and some, but not all, studies based in the UK. In several studies, researchers have had access to detailed clinical information which enabled them to assess the appropriateness of ICS use and subsequently conclude that ICS therapy was being overused .…”
Section: Discussionsupporting
confidence: 83%
“…Recent studies in diverse settings have found that prescribing practice does not conform to international or national COPD treatment guidelines, or drug licencing conditions . However, these investigations have been based on subgroups of patients drawn from selected general practices, health insurance databases, or respiratory outpatient clinics or hospitals, and none have examined the longitudinal patterns of use of long‐acting bronchodilator therapy in new users across an entire country.…”
Section: Introductionmentioning
confidence: 99%
“…Prescribing behaviours in human medicine have been studied to detect over-and under-prescription, links with adverse effects, and to characterise suboptimal antimicrobial stewardship in this age of increasing bacterial antimicrobial resistance [1][2][3][4][5][6]. Interrogation of medical records datasets is expedited and validated thanks to widespread use of embedded standardised clinical terminologies (e.g.…”
Section: Introductionmentioning
confidence: 99%